ORAL VERSUS INJECTABLE IRON THERAPY IN PATIENTS WITH CHRONIC KIDNEY DISEASE - SONAWANE, SHARAD B.; AGRAWAL, SACHIN; KUMAR, SUNIL (International Journal of Psychosocial Rehabilitation, 2020)
In CKD patients anaemia develops in begining stages due to decrease in production of erythropoietin by both kidneys. Patients with chronic kidney disease are at higher risk of developing iron deficiency due to decreased dietary intake, frequently testing of blood, decreased GI absorption and inflammation. [2] Oral and injectable iron have their advantages and disadvantages. Advantages of oral iron therapy are Convenient, cheapest, Easy to use, Safe and acceptable. However there are some advantages also like less bioavailability due to first pass effect, not used during emergency, cause gastric irritation, Metallic taste, Discoloration of teeth, Black colored stool.Injectable iron therapy also having some advantages like used in severe iron deficiency anemia, unable to tolerate oral iron, noncompliance, unable to absorb iron from gastrointestinal tract. And disadvantages are pain and discoloration of skin at injection site, arthralgia, lymphadenopathy, urticarial rash and anaphylaxis, in patients with active infection (fever).